Iman yang Mendialogkan Firman dalam Ruang Perjumpaan Multidimensional di Sekolah - Ompusunggu, Rusli; Sinambela, Rolan Sucipto; br. Sinaga, Riamin; Situmorang, Lerita; Damanik, Dapot (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2024)
This study examines the dynamic relationship between faith and scriptural dialogue within the multidimensional encounter spaces of educational institutions. The research explores how faith communities navigate the complexities of engaging with sacred texts while fostering meaningful dialogue across diverse theological, cultural, and pedagogical perspectives. Through qualitative analysis of educational practices, this study examines the methodological approaches used in creating inclusive spaces where the Word addresses contemporary educational challenges. The research reveals that effective faith-based dialogue requires sophisticated hermeneutical frameworks that honor both textual integrity and contextual relevance. Schools emerge as critical venues where traditional religious discourse meets modern educational paradigms, creating opportunities for transformative encounters. The findings demonstrate that the successful implementation of faith dialogue depends on establishing authentic relationships, maintaining theological depth while ensuring accessibility, and developing pedagogical strategies that respect diversity. This study contributes to understanding how educational institutions can serve as bridges between sacred traditions and contemporary learning environments, offering practical insights for educators seeking to integrate faith perspectives within pluralistic academic settings.   Abstrak Penelitian ini mengkaji hubungan dinamis antara iman dan dialog Firman dalam ruang perjumpaan multidimensional di institusi pendidikan. Studi ini mengeksplorasi bagaimana komunitas beriman menavigasi kompleksitas keterlibatan dengan teks suci sambil memupuk dialog bermakna lintas perspektif teologis, budaya, dan pedagogis yang beragam. Melalui analisis kualitatif praktik pendidikan, penelitian ini menyelidiki pendekatan metodologis yang digunakan dalam menciptakan ruang inklusif di mana Firman berjumpa dengan tantangan pendidikan kontemporer. Penelitian mengungkapkan bahwa dialog berbasis iman yang efektif memerlukan kerangka hermeneutis yang menghormati integritas tekstual dan relevansi kontekstual. Sekolah muncul sebagai tempat kritis di mana wacana religius tradisional bertemu paradigma pendidikan modern, menciptakan peluang perjumpaan transformatif. Temuan menunjukkan bahwa implementasi dialog iman yang berhasil bergantung pada pembentukan hubungan autentik, mempertahankan kedalaman teologis sambil memastikan aksesibilitas, dan mengembangkan strategi pedagogis yang menghormati keberagaman. Penelitian ini berkontribusi pada pemahaman bagaimana institusi pendidikan dapat berfungsi sebagai jembatan antara tradisi sakral dan lingkungan pembelajaran kontemporer.